Book Reviews / Comptes rendus (Food & History, 2023)
Book Reviews / Comptes rendus Paul JAMES, Food Provisions for Ancient Rome. A Supply Chain Approach (Abingdon/New York: Routledge, 2021), 240 pp., 29 b/w illus., ISBN 978-0-367-14339-8, reviewed by Dimitri VAN LIMBERGEN Shanshan WEN, Communal Dining in the Roman West: Private Munificence toward Cities and Associations in the First Three Centuries AD (Leiden: Brill, 2022), 321 pp., ISBN 978-9-004-51686-1, reviewed by John F. DONAHUE Béatrice CASEAU,Hervé MONCHOT (dir.), Religions et interdits alimentaires. Archéozoologie et sources littéraires (Louvain/Paris/Bristol, CT : Peeters, coll. Orient & Méditerranée n? 8, 2022), 250 pp., ISBN 978-9-042-94796-2, reviewed by Alban GAUTIER Marie-Claire FRÉDÉRIC, Le miel, une autre histoire de l’humanité (Paris : Albin Michel, 2022), 248 pp., ISBN 978-2-226-47049-2, reviewed by Maxime DELLIAUX Laura GIANNETTI, Food Culture and Literary Imagination in Early Modern Italy (Amsterdam: Amsterdam University Press, coll. Food Culture Food History before 1900, 2022), 260 pp., ISBN 978-9-463-72803-4, reviewed by Ryan WHIBBS Jennifer REGAN-LEFEBVRE, Imperial Wine. How the British Empire Made Wine’s New World (Berkeley: University of California Press, 2022), 342 pp., ISBN 978-0-520-34368-9, reviewed by Stéphane LE BRAS Bruno LAURIOUX,Kilien STENGEL (eds), Le modèle culinaire français. Diffusion, adaptations, transformations, oppositions dans le monde (XVIIe-XXIe siècles) (Tours : Presses universitaires François Rabelais, 2021), 252 pp., ISBN 978-2-869-06790-5, reviewed by Rachel RICH Jean-Pierre WILLIOT, Mobilités alimentaires. Restaurations et consommations dans l’espace des chemins de fer en France (XIXe-XXIesiècle) (Paris: Éditions de la Sorbonne, 2021), 288 pp., ISBN 979-1-035-10612-6, reviewed by Stefano MAGAGNOLI Darra GOLDSTEIN, The Kingdom of Rye: A Brief History of Russian Food (Oakland: University of California Press, 2022), 171 pp, ISBN 978-0-520-38389-0, reviewed by François-Xavier NÉRARD